IMPLEMENTASI STRATEGI PEMBELAJARAN INQUIRING MINDS WANT TO KNOW GUNA PENINGKATKAN AKTIVITAS BELAJAR SISWA KELAS X-7 SMA NEGERI 5 SURAKARTA - Sangadah, Ika Lailatus; Dwiastuti, Sri; Indrowati, Meti (P Biologi FKIP UNS Surakarta, 2011)
ABSTRACT ? The purposes of the research is to increase students learning activities through the implementation of inquiring minds want to know learning strategy in students of X-7 Class SMA Negeri 5 Surakarta School Years 2011/ 2012. This research is a Classroom Action Research with 2 cycle of action. Each cycle consisting of 4 phases which is planning, action, observation, and reflection. Observational subject is students of X-7 Class SMA Negeri 5 Surakarta school years 2011 / 2012. Observational data obtained from the questionnaire, observation, and interview. Technical analysis of data is using descriptive qualitative. Validate data by use of triangulation techic. Result of the research to prove that with action performing through learning strategy purpose inquiring minds want to know can increase students learning activities in students of X-7 Class SMA Negeri 5 Surakarta School Years 2011/ 2012. Averagely assesses percentage each indicator of students learning activities based on questionnaire data for pre cycle was 72,62%, first cycle was 78,07% (worked up 5,45%) and second cycle was 81,36% (worked up 3,29%). Meanwhile on a percentage point each indicator of students learning activities based on observation data for pre cycle was 71,31% and first cycle was 71,40% (worked up 0,09%). Averagely assesses percentage each indicator of students learning activities based on observation data for second cycle was 79,01% (worked up 8,61%). The result of interview with student indicates that implementation of inquiring minds want to know learning strategy can increase student curiousity by search in any information source. Base that result gets to be concluded that learning strategy purpose inquiring minds want to know can increase students learning activities of X-7 Class SMA Negeri 5 Surakarta School Years 2011/ 2012. Keywords : inquiring minds want to know learning strategy, students learning activities